Long-term impact of molecular epidemiology shifts of methicillin-resistant Staphylococcus aureus on severity and mortality of bloodstream infection - Norihito Kaku; Masaki Ishige; Go Yasutake; Daisuke Sasaki; Kenji Ota; Fujiko Mitsumoto-Kaseida; Kosuke Kosai; Hiroo Hasegawa; Koichi Izumikawa; Hiroshi Mukae; Katsunori Yanagihara (Emerging Microbes and Infections)
A 2019 nationwide study in Japan revealed the predominant methicillin-resistant Staphylococcus aureus (MRSA) types in bloodstream infections (BSIs) to be sequence type (ST)8-carrying SCCmec type IV (ST8-MRSA-IV) and clonal complex 1-carrying SCCmec type IV (CC1-MRSA-IV). However, detailed patient characteristics and how these MRSA types evolve over time remain largely unknown. In this long-term single-center study, MRSA strains isolated from blood cultures at Nagasaki University Hospital from 2012 to 2019 were sequenced and analyzed. Additionally, we compared the SCCmec types and patient characteristics identified in this study with previous data from our hospital spanning 2003–2007 and 2008–2011. Over this 16-year period, SCCmec type II decreased significantly from 79.2% to 15.5%, while type IV increased from 18.2% to 65.5%. This shift in SCCmec types was associated with notable changes in severity and outcomes; the sequential organ failure assessment (SOFA) score decreased from 5.8 to 3.1; in-hospital mortality declined from 39.8% to 15.5%. In contrast, no significant changes in patient demographics, such as age, sex, or underlying diseases, were observed. Between 2012 and 2019, the major combinations of SCCmec type and sequence type were ST8-MRSA-IV, ST8-MRSA-I, CC1-MRSA-IV, and ST5-MRSA-II. Additionally, ST8-MRSA-IV was divided into CA-MRSA/J, t5071-ST8-MRSA-IV, and USA300-like clone based on the results of molecular analysis. These major combinations showed similar drug resistance patterns, molecular characteristics, and phylogenetic features to those identified in nationwide surveillance. This study highlights the evolving nature of MRSA types in bloodstream infections, correlating with improved patient outcomes over time.